Power and mobility aware routing in wireless ad hoc networks - Tan, W. Chee-Wah (2013)
Nodes in a wireless ad hoc network have to support routing using their limited battery power resource. The routing protocol involved should use battery power efficiently for good system performance. For systems where node location information is available, this study proposes an on-demand routing protocol for choosing a route based on maximising the minimum node battery power and minimising the total transmission power required to reach the destination. In addition, the routing protocol proposed is able to restrict control packet flooding during route discovery and pre-empt link breakages because of node mobility. A power and mobility aware optimisation problem is first formulated. For an actual practical implementation, we present a heuristic scheme, Power and Mobility Aware Routing or PMAR protocol. PMAR performs almost as well as the proposed optimisation approach in static networks. In mobile networks, PMAR performs very well in terms of network lifetime, the number of data packets carried within the network lifetime and delay performance. It is shown to be energy efficient, effective in restricting control packet flooding and able to substantially reduce the network overheads caused by link breakages.